New Labour, new welfare state? : the "Third Way" in British social policy - Powell, Martin A., 1961- (Book collections on Project MUSE., 1999)
This study provides a comprehensive examination of the social policy of New Labour. It examines differences between current policy areas and provides topical information on the debate on the future of the welfare state.